EFFECT OF EXPOSURE BUILDUP FACTORS ON REACTOR SHIELDING - Abdulfattah, Adnan A (Al-Nahrain Journal of Science, 2010)
The gamma ray buildup factor for a point isotropic monoenrgetic source (0.1, 1 and 10 MeV) have been studied up to a depth of 10 mean free paths (mfp) for water, iron , lead and uranium dioxide (UO2). Also the exposure buildup factor for gamma radiation in heterogeneous (double layer) shielding were determined for different order of layer (layer closer to the source consist of either a low atomic number material followed by a high atomic number material or a high atomic number material followed by low atomic number material).